1996
DOI: 10.1046/j.1365-2958.1996.d01-1718.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐ordinate regulation of Salmonella typhimurium invasion genes by environmental and regulatory factors is mediated by control of hilA expression

Abstract: During infection of their hosts, salmonellae enter intestinal epithelial cells. It has been proposed that when Salmonella typhimurium is present in the intestinal lumen, several environmental and regulatory conditions modulate the expression of invasion factors required for bacterial entry into host cells. We report here that the expression of six different S. typhimurium invasion genes encoded on SPI1 (Salmonella pathogenicity island 1) is co-ordinately regulated by oxygen, osmolarity, pH, PhoPQ, and HilA. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
534
9

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(561 citation statements)
references
References 44 publications
(74 reference statements)
18
534
9
Order By: Relevance
“…Conversely, the PhoP/Q system that activates SPI-2 expression is known to shut down SPI-1 activity (Bajaj et al, 1996;Behlau and Miller, 1993). These and similar mechanisms are considered to coordinate the cross-talk between the different SPIs, with huge impact on Salmonella virulence (Fabrega and Vila, 2013).…”
Section: Salmonella As a Model Organism For Host-pathogen Interactionmentioning
confidence: 99%
“…Conversely, the PhoP/Q system that activates SPI-2 expression is known to shut down SPI-1 activity (Bajaj et al, 1996;Behlau and Miller, 1993). These and similar mechanisms are considered to coordinate the cross-talk between the different SPIs, with huge impact on Salmonella virulence (Fabrega and Vila, 2013).…”
Section: Salmonella As a Model Organism For Host-pathogen Interactionmentioning
confidence: 99%
“…Expression of SPI1 invasion and effector genes responds to multiple environmental signals and is decreased under conditions of high oxygen, low osmolarity, low pH, and stationaryphase growth (5,11,16,25). Many regulatory proteins influence invasion gene expression (31,32), but the key regulator is the SPI1-encoded HilA protein, which can activate their transcription directly (1,4,28) or by increasing expression of the activator InvF (9).…”
mentioning
confidence: 99%
“…Northern blotting indicated that the gene downstream of the prgH operon, orgA, did not reside on the same mRNA transcript nor did phoP appear to regulate levels of the orgA transcript, in contrast to the prgH transcript. However, work by another group indicated that an orgA::lacZY fusion is repressed by a phoP(Con) serovar strain of Typhimurium (3).…”
mentioning
confidence: 99%